1981
DOI: 10.1159/000117845
|View full text |Cite
|
Sign up to set email alerts
|

Use of Naloxone in Schizophrenic Psychoses and Manic Syndromes

Abstract: Since 1975, different morphinomimetic peptides have been isolated from hypophyseal-hypothalamic extracts: the pentapeptides methionine-enkephalin and leucine-enkephalin, and the longer peptides α-, β- and γ-endorphin. The primary structure of most of these peptides is also present in that of β-lipotropin. The morphinomimetic properties of endorphins can be blocked with opiate-antagonists. In rats, moreover, the endorphins influence behavior which cannot be blocked with opiate antagonists. On the basis of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1981
1981
1986
1986

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Beta-EP levels have been reported to be increased in the cerebro-spinal fluid or plasma of schizophrenic patients (Terenius etal. 1976;Domschke et al 1979;Emrich et al 1979) and the beta-EP antagonist naloxone was found to reduce auditory hallucinations in some patients (Verhoeven et al 1981). Other reports have suggested a state of beta-EP deficiency in schizophrenia (Kline et al 1977).…”
mentioning
confidence: 99%
“…Beta-EP levels have been reported to be increased in the cerebro-spinal fluid or plasma of schizophrenic patients (Terenius etal. 1976;Domschke et al 1979;Emrich et al 1979) and the beta-EP antagonist naloxone was found to reduce auditory hallucinations in some patients (Verhoeven et al 1981). Other reports have suggested a state of beta-EP deficiency in schizophrenia (Kline et al 1977).…”
mentioning
confidence: 99%
“…Since the single-blind study by Gunne et al (1977), in which schizophrenie patients experienced decreased audi• tory hallucinations after naloxone administration, the effects of the opiate antagonist in schizophrenie patients have been investigated in numerous double-blind studies. Some authors have reported that naloxone reduced psycho• tic syndromes (Berger et al, 1981;Emrich et al, 1977;Jorgensen and Cappelen, 1982;Lehmann et al, 1979;Watson et al, 1978), while others found only marginal therapeutic effects (Davis et al, 1977;Kleinman et al, 1982;Pickar et al, 1982) or no placebo-naloxone differences (Janowsky et al, 1977;Kurland et al, 1977;Lipinski et al, 1979;Sethi and Prakash, 1981;Verhoeven et al, 1981, Volavka et al, 1977. These controversial studies differ considerably in patient population, duration of observation and dosage.…”
mentioning
confidence: 99%